Amorphous silicon dioxide two-dimensional material and preparation method thereof
By using prepolymerized raw materials such as tetraethyl silicate, self-assembly reaction and template removal methods, high-quality amorphous silica two-dimensional materials were prepared, solving the problems of complex preparation processes and low yields in the prior art, and achieving high-efficiency and low-cost large-scale preparation.
Patent Information
- Application Number
- CN202410481189.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-04-22
AI Technical Summary
The prior art is difficult to efficiently and at low cost to prepare high-quality two-dimensional silica materials, and the preparation process is complex and the output is low.
Prepolymerized tetraethyl silicate, ethyl acetate and alkaline sources are used as raw materials to prepare amorphous silica two-dimensional material precursors through self-assembly reactions, and the template is removed by methods such as high temperature, chemical etching and electrochemical corrosion to prepare amorphous silica two-dimensional material.
Amorphous silica two-dimensional material with excellent high temperature resistance, simple preparation technology, and large-scale preparation, with an output of 100-10,000 times, high material quality, adjustable morphology and size.
Smart Images

Figure CN118270794B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of two-dimensional materials, and specifically relates to amorphous silicon dioxide two-dimensional materials and a preparation method thereof. Background Art
[0002] Two-dimensional materials are a special type of material whose constituent atoms are tightly bound by covalent or ionic bonds in the same plane, while the layers are connected by weak van der Waals interactions. When the material thickness is reduced to the atomic level, the confinement effect in the thickness direction will be significantly highlighted, thus exhibiting a variety of physical properties. Compared with layered compounds that can be prepared by top-down peeling methods, crystalline materials have strong covalent or ionic bonds in three dimensions. It is difficult to find layered precursors for such materials in nature, so the top-down method is not applicable to them, so they can only be prepared by vapor deposition or molecular beam epitaxy. However, the above preparation methods have strict requirements on the preparation process, high preparation cost and low yield (usually milligram level) [Carvalho, A, Neto C, et al. 2D materials and van der Waalsheterostructures [J]. Science, 2016.].
[0003] Although significant progress has been made in the study of two-dimensional materials, this rapidly developing field still faces some major challenges: 1) The properties and applications of two-dimensional materials are highly related to their structural characteristics (such as size, number of layers, doping, defects, vacancies, interlayer spacing, crystal phase and crystallinity, etc.), so how to synthesize two-dimensional materials with target structural characteristics in a highly controllable manner is one of the biggest challenges; 2) The lateral size and atomic-level thickness of two-dimensional materials give them many excellent properties, so how to prepare two-dimensional materials with controllable size and number of layers (thickness) is another major challenge; 3) Two-dimensional materials are extremely easy to stack together during storage and application, which will greatly weaken their advantages, so how to prevent the stacking of two-dimensional materials is an urgent problem to be solved; 4) Another challenge is how to achieve low-cost, large-scale preparation of high-quality two-dimensional materials.
[0004] Thanks to their amorphous properties (non-crystalline state) and ultra-thin two-dimensional structure, amorphous two-dimensional materials exhibit many unique and excellent properties compared to traditional crystalline two-dimensional materials, which can be attributed to: 1) Rich defects. Due to the randomness of the atomic arrangement during the growth of amorphous materials, a large number of defects will be generated inside and on the surface of the material. The generation of defects means that the material has a large number of physical and chemical reaction active sites; 2) Controllable electronic state. The disorder of atomic arrangement will affect the original coordination and chemical bonds, thereby increasing the activity of electrons; 3) Rapid transmission of electrons. Amorphous structure can provide other transmission modes for electron transmission; in addition, combined with the atomic-scale thickness of two-dimensional materials, it helps to shorten the electron transmission distance.
[0005] Silicon dioxide (SiO2) plays a very important role in key fields such as semiconductors and integrated circuits, new energy, aerospace, biomedicine and scientific research. For example, silicon dioxide is often used as an insulating layer material in semiconductor and integrated circuit manufacturing to isolate different electronic components to avoid current interference between circuit components. Therefore, it is particularly important in integrated circuits [Rojas S, Modelli A, Wu WS, et al. Properties of silicon dioxide films prepared by low-pressure chemical vapor deposition from tetraethylorthosilicate [J]. Journal of vacuum science & technology B, 1990, 8 (6): 1177-1184.]; in addition, silicon dioxide is also widely used as a floating gate oxide for manufacturing gates in flash memory and dynamic random access memory (DRAM) [Selberherr, Siegfried. Analysis and simulation of semiconductor devices [M]. Springer-Verlag Wien, 1984.]. In the field of new energy, due to its simple preparation method and high theoretical specific capacity, silica is used as anode material and diaphragm modification material for secondary batteries such as lithium batteries [Yao Y, Zhang J, Xue L, et al. Carbon-coated SiO2 nanoparticles as anode material for lithium ion batteries [J]. Journal of Power Sources, 2011 (23).]. Due to its excellent high temperature resistance and heat insulation properties, silica aerogel is also used as heat insulation and flame retardant material between power battery cells, heat insulation and shockproof material between module and shell, and external cold and high temperature insulation layer material of battery box [Li L, Zhou Y, Gao Y, et al. Large-scale assembly of isotropic nanofiber aerogels based on columnar-equiaxed crystal transition [J]. Nature Communications, 2023, 14].In the field of aerospace, due to its high temperature resistance and thermal stability, silica is often used as a thermal protection coating on the surface of spacecraft to protect the spacecraft from high temperature when re-entering the atmosphere [Houdayer A, Cerny G, Klemberg-Sapieha JE, et al,. MeV proton irradiations and atomic oxygen exposure of spacecraft materials with SiO 2protective coatings [J]. Nuclear Instruments & Methods in Physics Research, 1997, 131 (1-4): 335-340]. In biomedicine, silica nanomaterials are often used as effective carriers for drug delivery to improve the efficacy of drugs by regulating the release rate and increasing bioavailability [Fang qiong, Tang Linlin, et al,. Mesoporous silica nanoparticles: synthesis, biocompatibility and drug Delivery [J]. Advanced Materials, 2012.].
[0006] In recent years, researchers have developed silica materials with a variety of morphologies, including spheres, rods, wires, and flakes. In general, the prepared silica is mainly one-dimensional and three-dimensional, while two-dimensional silica is less studied. This is because in the self-assembly process of the material, the spherical structure has the smallest surface energy, so the material generally preferentially forms a spherical structure. At present, the preparation method of two-dimensional silica thin film materials mainly adopts vapor deposition technology, which requires the use of expensive production equipment and has strict requirements on the preparation process and growth substrate. More importantly, the material prepared by vapor deposition technology has a low yield (usually milligram level).
[0007] In summary, two-dimensional silica thin film materials play an important role in key fields such as semiconductors and integrated circuits, biomedicine, aerospace, and scientific research. The preparation and development of two-dimensional silica thin film materials directly affect the development of the above fields. Amorphous silica two-dimensional materials have unique advantages in physical and chemical properties, but there are huge challenges in their large-scale preparation. It is urgent to develop a new method for large-scale preparation of high-quality amorphous silica two-dimensional materials and to regulate their morphology and size to meet the needs of practical applications. It plays a very important role in promoting the development of key fields such as semiconductors and integrated circuits, biomedicine, aerospace, and scientific research. Summary of the invention
[0008] In view of the deficiencies in the prior art, the present invention proposes an amorphous silicon dioxide two-dimensional material and a preparation method thereof which has excellent high temperature resistance, a simple preparation process, and can be prepared on a large scale.
[0009] The method for preparing an amorphous silicon dioxide two-dimensional material provided by the present invention uses prepolymerized tetraethyl silicate (TEOS), ethyl acetate and an alkali source as raw materials to prepare an amorphous silicon dioxide two-dimensional material precursor through a self-assembly reaction; utilizes a sacrificial template method such as high temperature, chemical etching and electrochemical corrosion to remove the template to obtain an amorphous silicon dioxide two-dimensional material; the specific steps are as follows:
[0010] S1, adding prepolymerized tetraethyl silicate and ethyl acetate in a certain volume ratio into an alkaline solution, and stirring magnetically for 3-10 hours to obtain a milky white silica precursor solution;
[0011] S2, washing the solution in S1 by centrifugation with deionized water, collecting and obtaining a milky white precipitate, and then dispersing the above pure silica milky white precipitate in a solvent and storing it for later use;
[0012] S3, mixing the silica precursor solution in S2 with the template material solution in a certain proportion, and magnetically stirring for 3-5 hours to fully mix to obtain a mixed solution; freeze-drying the mixed solution for 4-200 hours to obtain a mixed powder of silica and template material;
[0013] S4, removing the template material in the mixed powder obtained in S3 to obtain a white amorphous silica two-dimensional material.
[0014] Further:
[0015] The volume ratio of the prepolymerized tetraethyl silicate (TEOS) to ethyl acetate is 0.0001-10000, preferably 1:1.
[0016] The alkaline solution is selected from sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, sodium bicarbonate, etc., preferably sodium hydroxide solution.
[0017] The pH value of the alkaline solution is 7.5-14, preferably 12.
[0018] The rotation speed of the centrifugal washing is 100-100000.
[0019] The solvent is selected from deionized water, anhydrous ethanol, isopropanol, acetone, acetonitrile, chloroform, dichloromethane, ether, toluene, cyclohexane, hexane, N,N-dimethylformamide, etc., preferably deionized water and anhydrous ethanol.
[0020] The concentration ratio of the silicon dioxide precursor solution to the template material is 0.0001-10000, preferably 0.1:1.
[0021] The template material is selected from graphene oxide, reduced graphene oxide, carbon fiber, carbon cloth, carbon fiber paper, wood fiber, foamed nickel, foamed iron, foamed copper, polyvinyl alcohol, polystyrene, etc., and the preferred material is graphene.
[0022] The template removal method is high temperature ablation, chemical dissolution etching, electrochemical corrosion, etc., and the preferred method is high temperature ablation.
[0023] The preparation method of the present invention prepares a size-adjustable amorphous silicon dioxide two-dimensional material by adjusting the size of the ablation template; by adjusting the concentration of the precursor solution, the adhesion concentration of the silicon dioxide precursor on the template can be regulated, thereby regulating the thickness and morphology of the finally prepared amorphous silicon dioxide two-dimensional material; the adjustable thickness range is 1nm-10nm; the adjustable flake diameter range is 1μm-40μm.
[0024] In the above S1 and S2, by selecting template materials such as graphene, which are widely available and in large quantities, large-scale preparation of amorphous silicon dioxide two-dimensional materials can be achieved.
[0025] In the above S3 and S4, TEOS is prepolymerized in advance to obtain a silicon dioxide sheet material precursor by self-assembly; while using non-prepolymerized TEOS as a raw material, only silicon dioxide particles but not sheet morphology will be obtained.
[0026] The amorphous silicon dioxide two-dimensional material prepared by the present invention has the characteristics of excellent high temperature resistance (can withstand temperatures above 1,000 degrees Celsius for a long time), thermal insulation, good semiconductor properties and biocompatibility. It has broad application prospects in key fields such as semiconductors and integrated circuits, biomedicine, aerospace and scientific research.
[0027] For example, the amorphous silica two-dimensional material is prepared into a high-temperature resistant aerogel material that can withstand high temperatures of 800-1700°C.
[0028] Compared with the prior art, the main advantages of the present invention are:
[0029] (1) Solved the technical bottleneck problem of preparing two-dimensional silicon dioxide materials;
[0030] (2) Traditional two-dimensional materials can only produce a few milligrams or tens of milligrams of material at a time; the method of the present invention can produce a volume of 1 liter of material (mass of 10 grams) at a time under the conditions of existing experimental equipment, and the output is increased by 100-10,000 times; it should be pointed out that the upgrade of experimental equipment can realize the larger-scale preparation of amorphous silicon dioxide two-dimensional materials;
[0031] (3) The continuous preparation method of the present invention has high yield, simple process, low price and high economic benefit;
[0032] (4) The prepared silica two-dimensional material is amorphous, which fills the gap in the preparation technology of amorphous silica two-dimensional materials and provides the required materials and technical support for subsequent research on amorphous silica two-dimensional materials;
[0033] (5) The prepared amorphous silica two-dimensional material is of high quality and exhibits flexible properties of bendable wrinkles. Its morphology, size and thickness can be adjusted as needed; it is completely different from other rigid two-dimensional materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Optical photograph of amorphous silica two-dimensional material prepared on a large scale with a volume of 1 liter.
[0035] Figure 2 X-ray powder diffraction pattern and electron paramagnetic resonance spectrum of amorphous silicon dioxide two-dimensional material.
[0036] Figure 3 Transmission electron micrograph of amorphous silicon dioxide two-dimensional material.
[0037] Figure 4 This is a scanning electron micrograph of the 40 μm-diameter amorphous silicon dioxide two-dimensional material prepared in Example 2.
[0038] Figure 5 This is a scanning electron micrograph of the 15 μm-diameter amorphous silicon dioxide two-dimensional material prepared in Example 2.
[0039] Figure 6 This is an atomic force micrograph of the amorphous silicon dioxide two-dimensional material with a thickness of 10 nm prepared in Example 3.
[0040] Figure 7 This is an atomic force micrograph of the amorphous silicon dioxide two-dimensional material with a thickness of 4 nm prepared in Example 3.
[0041] Figure 8 This is an atomic force micrograph of the amorphous silicon dioxide two-dimensional material with a thickness of 2 nm prepared in Example 3.
[0042] Fig. 9 This is an atomic force micrograph of the amorphous silicon dioxide two-dimensional material with a thickness of 1.3 nm prepared in Example 3.
[0043] Fig.10 This is an optical photograph of the ultralight amorphous silica aerogel material prepared in Example 4.
[0044] Fig.11This is a photograph of the high temperature resistance experiment of the ultralight amorphous silica aerogel material prepared in Example 4. DETAILED DESCRIPTION
[0045] The present invention is further described below by way of embodiments in conjunction with the accompanying drawings, but is not limited to the embodiments.
[0046] The terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art.
[0047] In the following examples, various processes and methods not described in detail are conventional methods well known in the art.
[0048] Example 1
[0049] The method uses graphene oxide as a sacrificial template to prepare amorphous silica two-dimensional material on a large scale, including adding prepolymerized tetraethyl silicate (TEOS) and ethyl acetate to an alkaline solution of a certain pH value, and obtaining a milky white silica solution after magnetic stirring for 3 hours. The above solution is centrifuged and washed with deionized water and collected to obtain a milky white precipitate, and finally the white silica precipitate is dispersed in a solvent and stored for later use. The specific steps are:
[0050] S1: Prepare 2 mol / L sodium hydroxide solution: weigh 0.8 g of sodium hydroxide solid and fully dissolve it in 10 mL of deionized water, then add it into 500 mL of deionized water under stirring and stir to mix evenly;
[0051] S2: Based on S1, 10 mL of prepolymerized tetraethyl silicate (TEOS) was added under stirring, and then 10 mL of ethyl acetate was slowly injected;
[0052] S3: Based on S2, the above solution was magnetically stirred for 3 hours to obtain a milky white solution;
[0053] S4: centrifugally clean and collect the milky white solution obtained in S3 to obtain a milky white precipitate, and dissolve and disperse the precipitate in deionized water for later use;
[0054] S5: adding the S4 silica aqueous solution to the graphene oxide aqueous solution to make the concentration ratio of the two to be 1:1, and mixing them evenly by magnetic stirring;
[0055] S6: The miscible solution of S5 is frozen into a solid with liquid nitrogen, and then freeze-dried for 48 hours to obtain silicon dioxide powder supported on graphene oxide;
[0056] S7: Place the S6 powder in a muffle furnace, raise the temperature to 700°C at 5°C / min, and keep it at 700°C for 24 hours to fully ablate and remove the graphene oxide, and then obtain a white amorphous silicon dioxide two-dimensional material.
[0057] Figure 2 The X-ray powder diffraction pattern and electron paramagnetic resonance spectrum of the amorphous silicon dioxide two-dimensional material prepared in this example are: Figure 3 Transmission electron micrograph.
[0058] Example 2
[0059] A large-scale preparation of an amorphous silicon dioxide two-dimensional material with adjustable sheet diameter, the specific steps are:
[0060] S1, adding the silicon dioxide aqueous dispersion obtained in S4 in the above Example 1 to the graphene oxide dispersions with a flake diameter of 50 μm and 20 μm respectively, so that the concentration ratio of the two is 1:1, and mixing them evenly by magnetic stirring;
[0061] S2: The miscible solution of S1 was frozen into a solid with liquid nitrogen, and then freeze-dried for 48 hours to obtain silicon dioxide powder supported on graphene oxide;
[0062] S3: Place the S2 powder in a muffle furnace, raise the temperature to 700°C at 5°C / min, and keep it at 700°C for 24 hours to fully ablate and remove the graphene oxide, and then obtain white amorphous silicon dioxide two-dimensional materials with sheet diameters of 40μm and 15μm respectively.
[0063] Figure 4 , Figure 5 They are scanning electron micrographs of 40 μm and 15 μm flake diameter amorphous silicon dioxide two-dimensional materials prepared in Example 2, respectively.
[0064] Example 3
[0065] The large-scale preparation of amorphous silicon dioxide two-dimensional materials with adjustable thickness, the specific steps are:
[0066] S1, adding the silica aqueous dispersion obtained in S4 in the above Example 1 to the graphene oxide dispersion with a flake diameter of 2 μm, controlling the concentration ratio of the silica aqueous dispersion to the graphene oxide to be 0.1:1, 0.2:1 and 1:1, respectively, and mixing them uniformly by magnetic stirring;
[0067] S2: The three mixed solutions of S1 were frozen into solids with liquid nitrogen, and then freeze-dried for 48 hours to obtain three types of silica powders loaded on graphene oxide;
[0068] S3: The three powders of S2 were placed in a muffle furnace, and the temperature was raised to 700°C at a rate of 5°C / min. The temperature was kept at 700°C for 24 hours to fully ablate and remove the graphene oxide, and then white amorphous silicon dioxide two-dimensional materials with thicknesses of 4nm, 2nm, and 1.3nm were obtained.
[0069] Figure 6 , Figure 7, Figure 8 , Fig. 9 Atomic force micrographs of amorphous silicon dioxide two-dimensional materials with thicknesses of 10 nm, 4 nm, 2 nm, and 1.3 nm prepared in this embodiment, respectively.
[0070] Example 4
[0071] The amorphous silicon dioxide two-dimensional material prepared by the present invention is used to prepare a lightweight, heat-insulating and high-temperature resistant aerogel material, and the specific steps are as follows:
[0072] S1, adding the silicon dioxide aqueous dispersion obtained in S4 in the above Example 1 to the graphene oxide dispersion with a flake diameter of 40 μm, controlling the concentration ratio of the silicon dioxide aqueous dispersion to the graphene oxide to be 2:1, and mixing them uniformly by magnetic stirring;
[0073] S2: Pour the mixed solution in S1 into a special mold, and then put it into a vacuum oven to evacuate for about 10 minutes to remove bubbles in the solution;
[0074] S3: placing the mold containing the solution in S2 in liquid nitrogen, so that the water in the mixed solution grows directionally into ice crystals at low temperature; after the solution completely turns into a solid at low temperature, placing it in a -20°C refrigerator for storage;
[0075] S4: freeze-drying the solid ice crystal material obtained in S3 for 48 hours to obtain a composite aerogel of silicon dioxide and graphene oxide;
[0076] S5: The S4 composite aerogel was placed in a muffle furnace, heated to 700°C at a rate of 5°C / min, and kept at 700°C for 24 hours to fully ablate and remove the graphene oxide, and then a white amorphous silica two-dimensional aerogel material was obtained.
[0077] The optical photograph of the ultralight amorphous silica aerogel material prepared in this example is shown in Fig.10 The high temperature resistance test results are shown in Fig.11 .
Claims
1. A method for preparing an amorphous silicon dioxide two-dimensional material, characterized in that: Using prepolymerized tetraethyl silicate, ethyl acetate and an alkali source as raw materials, an amorphous silicon dioxide two-dimensional material precursor is prepared by self-assembly reaction; the specific steps are: S1, adding prepolymerized tetraethyl silicate and ethyl acetate into an alkaline solution, and magnetically stirring for 3-10 hours to obtain a milky white silica precursor solution; S2, washing the solution in S1 by centrifugation with deionized water, collecting and obtaining a milky white precipitate, and then dispersing the above pure silica milky white precipitate in a solvent and storing it for later use; S3, mixing the silica precursor solution in S2 with the template material solution, and magnetically stirring for 3-5 hours to fully mix, to obtain a mixed solution; The mixed solution is freeze-dried for 4-200 hours to obtain a mixed powder of silicon dioxide and a template material; the template material is selected from graphene oxide; S4, removing the template material in the mixed powder obtained in S3 by high temperature ablation to obtain a white amorphous silicon dioxide two-dimensional material.
2. The preparation method according to claim 1, characterized in that: The volume ratio of prepolymerized tetraethyl silicate to ethyl acetate in step S1 is 1:
1.
3. The preparation method according to claim 1, characterized in that: The pH value of the alkaline solution in step S1 is 7.5-14, and is selected from sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, and sodium bicarbonate.
4. The preparation method according to claim 1, characterized in that: The solvent in step S2 is selected from deionized water, anhydrous ethanol, isopropanol, acetone, acetonitrile, chloroform, dichloromethane, ether, toluene, cyclohexane, hexane, and N,N-dimethylformamide.
5. The preparation method according to claim 1, characterized in that: The concentration ratio of the silicon dioxide precursor solution to the template material in step S3 is 0.1:1, 0.2:1, 1:1 or 2:
1.
6. The preparation method according to claim 1, characterized in that: By adjusting the size of the ablation template, size-adjustable amorphous silica two-dimensional materials can be prepared; by adjusting the concentration of the precursor solution, the adhesion concentration of the silica precursor on the template can be controlled, thereby controlling the thickness and morphology of the final prepared amorphous silica two-dimensional material; the adjustable thickness range is 1 nm-10 nm; the adjustable flake diameter range is 1 μm-40 μm.
7. An amorphous silicon dioxide two-dimensional material obtained by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Au@SiO2 mesoporous composite nanomaterial and preparation method thereof
CN105174272A
2D lamellar structure silica-based desulfurization catalyst and preparation method thereof
CN114849777A